ANALISIS STRATEGI PEMELIHARAAN SUMBER DAYA MANUSIA - Aprilia, Ade Sabrina Ayu; Risca, Rindi; Ghofur, Abdul; Hakim, Adi Lukman (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2025)
This article discusses the importance of human resource maintenance (HRM) as an organizational strategy to maintain productivity and sustainability. The study focuses on the concepts, objectives, and principles of HRM, workload and job satisfaction analysis, and the role of employee counseling. The research applies theories from Hasibuan, Robbins & Judge, Mathis & Jackson, and previous studies, using a literature review and qualitative analysis. The findings indicate that HRM includes compensation, safety, and welfare, and is based on the principles of benefit, justice, satisfaction, legality, and company capability. A balanced workload positively influences job satisfaction, while counseling supports employees’ mental health and motivation. Therefore, HRM is considered a strategic investment to enhance loyalty, reduce turnover, and develop a productive and adaptive workforce.